Ivory Gull (Pagophila eburnea) Distribution in Late Summer and Autumn in Eastern Lancaster Sound and Western Baffin Bay - Renaud, Wayne E.; McLaren, Peter L. (ARCTIC, 1982)
Ivory gulls in western Baffin Bay and eastern Lancaster Sound were studied in 1976, 1978 and 1979 using aerial surveys. During September and October concentrations of hundreds of ivory gulls occurred along glacier fronts on southeast Ellesmere and northeast and southeast Devon islands, and where offal was available near the settlements of Grise Fiord and Pond Inlet. Dispersal (= southward migration) from coastal to offshore areas proceeded as pan ice cover increased in offshore areas, usually in late September or early October in Lancaster Sound and in mid-October in Baffin Bay east of Baffin Island. Lancaster Sound and northwest Baffin Bay may be a major autumn migration route for ivory gulls that breed in the central and eastern High Arctic and winter in southern Davis Strait and areas to the south.Key words: ivory gull, Pagophila eburnea, autumn status, migration, Baffin Bay, Lancaster Sound, glacier fronts, aeriel surveys